A first course in differential equations, modeling, and simulation - Smith, Carlos A. (CRC Press, 2011)
"Overcoming some of the drawbacks in standard differential equations courses, this text illustrates the development of dynamic models using basic physics and analytical solution and simulation methods. Taking a rigorous yet practical approach, the authors clearly explain how to solve differential equations and emphasize the integration of modeling and simulation. The book develops models of physical systems, before obtaining the analytical solution and performing simulations. The examples and problems provided encourage real-world design experience"--Provided by publisher.